PENINGKATAN ARUS LISTRIK DAN TEGANGAN LISTRIK KELUARAN SEL SURYA DENGAN MENGGUNAKAN REFLEKTOR - Ratna Dwi Rahayu (Sekolah Tinggi Teknologi Ronggolawe Cepu, 2022)
The output solar cells in the form of electric current and voltage as an alternative energy source can be increased by increasing the intensity of the light that falls on the surface of the solar cell. The intensity of light falling on the solar cell can be magnified by using a reflector. This article analyses in the magnitude of the electric current and voltage output of solar cells using a reflector in the form of a flat mirror at a mirror angle of 600 and a concave mirror with a focal length of 20 cm againt the output of a solar cell without a reflactor. The measurement results show that there ia a greater increase in output by using a flat mirror compared to using a concave mirror as a reflector. Increasing the magnitude of the electric current and output voltage of solar cells with a flat mirror as a reflector to the electric current and output voltage of solar cells without reflectors was 3,54 % and 29,28 %, respectively on the use of a concave mirror as a reflector of 1,7 % and 9,98 %.